Association of a Liver Allocation Policy Change With Domestic Travel for Liver Transplantation - Katie Ross-Driscoll, PhD, MPH; Chandrashekhar Kubal, MD, PhD; Arrey-Takor Ayuk-Arrey, MPH; Jonathan Fridell, MD; David Axelrod, MD, MBA (Transplantation Direct)
Background. In 2020, liver allocation policy in the United States was changed to allow for broader organ sharing, which was hypothesized to reduce patient incentives to travel for transplant. Our objective was to describe patterns of travel for domestic liver transplant pre- and post–acuity circle (AC) implementation. Methods. Incident adult liver transplant listings between August 16, 2016, and February 3, 2020 (pre-AC) or June 13, 2020, and December 3, 2023 (post-AC) were obtained from the Scientific Registry of Transplant Recipients. We used previously defined geographic catchment areas to classify patients as (1) no travel, (2) travel to a neighboring region, and (3) travel beyond a neighboring region. We used multinomial logistic regression to identify characteristics associated with travel and cause-specific hazards modeling to estimate the association between travel and time to deceased donor transplant, stratified by model for end-stage liver disease (MELD) score and AC era. Results. Among 83 033 liver candidates, 76% were listed in their home region. Black race, lower educational attainment, increased neighborhood social deprivation, and Medicaid were significantly associated with decreased odds of traveling beyond a neighboring region. After AC, traveling beyond a neighboring region was associated with an increased hazard of transplant for patients with a MELD score <15 (cause-specific hazard ratio [csHR]: 1.25; 95% confidence interval [CI], 1.11-1.40), MELD score 15–24 (csHR: 1.19; 95% CI, 1.07-1.31), and MELD score 25–34 (csHR: 1.15; 95% CI, 1.01-1.32). Conclusions. Travel frequency, geographic patterns of travel, and characteristics associated with travel were largely unchanged after AC. Changes to allocation policy alone may not equalize patient means or desire to travel for transplant care.